Pengaruh Citra Perusahaan dalam Mempertahankan Eksistensi UMKM Pekalongan di Masa Pandemi Covid-19 dan Era New Normal - Wenti Ayu Sunarjo; Amalia Ilmiani; Siti Nurhayati (Jurnal Manajemen dan Keuangan, 2021)
The impact felt during the spread of the corona virus was very large, especially on the country's economy, one of the most vulnerable sectors is MSMEs which are the driving force of the country's economy. Consumers began to limit their consumption due to deteriorating financial conditions. Moreover, consumers really want satisfaction when choosing MSMEs that are considered able to provide prices that are in accordance with financial conditions during the Covid-19 pandemic, are able to provide good service, and are able to maintain the company's existence by creating a positive image, so that consumers feel satisfied. The purpose of this study is to examine the impact of the Covid-19 outbreak on the MSME business, how people are consistent in using Indonesian MSME products because they are familiar with their image and quality, so that MSMEs can still maintain their existence in the face of crises in that era. The level of technological readiness in research This is at the basic research stage with the output target is to obtain data from a questionnaire about how great the existence of Indonesian local MSMEs is able to survive during the COVID-19 pandemic until a new era is normal. The sample used in the study used a random sampling technique to randomly select consumers of Indonesian local MSME products throughout Indonesia, with data analysis techniques using Structural Equation Modeling (SEM). The result is that company image is able to mediate service quality on customer satisfaction, but is not proven to mediate customer satisfaction prices. This opens the door for future research.